2021
DOI: 10.21873/invivo.12651
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Biomonitoring in Buccal Mucosa Cells of COVID-19 Patients: Preliminary Findings

Abstract: Background/Aim: COVID-19 may lead to progressive respiratory failure as a consequence of alveolar damage, resulting in death. The aim of this study was to evaluate cytogenetic damage in oral cells of COVID-19 patients by micronucleus assay. Patients and Methods: A total of 11 COVID-19 patients aged 40.7±9.3 years (5 men and 6 women) were included in this study. For the control group, a total of 15 participants not infected with SARS-CoV-2 virus were included. The mean age was 41.6±6.2 years (5 men and 10 women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Our results are consistent with previously published data on DNA damage in severely ill patients with multiple trauma [ 21 ] and sepsis [ 40 ], in which the level of multiple organic dysfunctions has been shown to positively correlated with DNA damage. Similar, Pinto concluded that SARS-CoV-2 virus could promote mutagenesis by increasing in micronuclei-bearing cells in buccal mucosa of 11 patients with COVID-19 [ 41 ].…”
Section: Discussionmentioning
confidence: 98%
“…Our results are consistent with previously published data on DNA damage in severely ill patients with multiple trauma [ 21 ] and sepsis [ 40 ], in which the level of multiple organic dysfunctions has been shown to positively correlated with DNA damage. Similar, Pinto concluded that SARS-CoV-2 virus could promote mutagenesis by increasing in micronuclei-bearing cells in buccal mucosa of 11 patients with COVID-19 [ 41 ].…”
Section: Discussionmentioning
confidence: 98%
“…One study was done on the MN frequency in acute SARS-CoV-2 viral infections as a pilot study between COVID-19 infected patients and healthy subjects concluding a significant increase in the number of MN in COVID-19 infected patients and thus proving SARS-CoV-2 is causing cytotoxicity to epithelial cells. [ 27 ] Even to be more specific, the present study was done in symptomatic patients (symptomatic COVID-19 positive and symptomatic COVID-19 negative) and there was a significant increase in MN count thus confirming the cytogenotoxicity of SARS-CoV-2 virus than any other microorganisms causing flu-like illness.…”
Section: Discussionmentioning
confidence: 53%
“…Pinto et al . 2021[ 27 ] showed only karyolytic and karyorrhexic cells were significantly higher in COVID-19 positive patients than in healthy controls. The karyolysis and karyorrhexis, which are induced by SARS-CoV-2, are closely associated with necrosis and apoptosis due to very high insult.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, IHC analysis of lip tissues with blister-like lesions showed that SARS-CoV-2 spike protein was positive in minor salivary acinus and duct cells ( 125 ). Interestingly, micronucleus test demonstrated that the death of oral mucosal cells was induced by SARS-CoV-2 ( 126 ). These indicate that SARS-CoV-2 induces cell death when it infects the salivary glands.…”
Section: Pathogenic Mechanisms In Covid-19mentioning
confidence: 99%